Biophysical Mechanism Determining Dental Implants Biocompatibility and Conditioning their Osseointegration - S. Bartáková; P. Prachár; S. Hasoň; R. Silvennoinen; L. Cvrček; L. Strašák; L. Fojt; A. Avranas; V. Vetterl (Czech Dental Chamber, 2009)
Adsorption of biopolymers at the titanium and titanium carbide surface increases the optical roughness as well as the thickness and refractive index of the surface layer. Fibrinogen is better adsorbed at the titanium surface which is treated by polishing and etching than at the surface treated only by polishing. The best adsorption of fibrinogen was observed at the titanium carbide surface prepared by plasma-enhanced chemical vapour deposition, the optimal ratio was Ti0,38 - C0,62 a Ti0,09 - C0,91. The surface of dental implants treated by this way should speed up their osseointegration and healing. The single stranded pyrimidine oligodeoxynucleotides (TTC)12 are better adsorbed at the titanium surface than the purine oligodeoxynucleotides (AAG)12. The double-helical duplex (TTC)12. (AAG)12 has no effect on the optical properties of the titanium surface and probably is not adsorbed there.